The Role of Intellectual Capital and Knowledge Management in Enhancing FMCG Firm Performance - Aburizal Maharsyah; Ignatius Trisna Adi; Sahwa Putri Utami; Syarifa Hanoum; Thedosia Yunita Durman (Universitas Mercu Buana, 2026)
This study aims to analyze the role of Intellectual Capital (IC) and Knowledge Management (KM) in influencing Firm Performance (FP) in companies within the Fast-Moving Consumer Goods (FMCG) sector.A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 104 respondents across various job levels. The results indicate that both IC and KM have a positive and significant impact on FP. Furthermore, KM was found to partially mediate the relationship between IC and FP, implying that a firm’s success is not only determined by intellectual capital but also by its ability to manage and utilize knowledge effectively. This study contributes to the development of IC and KM literature by highlighting the mediating role of KM in enhancing firm performance, particularly in the FMCG sector. The findings provide practical insights for managers in designing and implementing knowledge-based strategies that integrate IC and KM to strengthen firm performance and build sustainable competitive advantage in dynamic markets. The study is limited by its sample size and focus on the FMCG sector. Future research may expand to other industries and employ longitudinal data to capture performance dynamics over time.